2020
DOI: 10.3934/dcdss.2020131
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of an equation with two delays and application to the production of platelets

Abstract: We analyze the stability of a differential equation with two delays originating from a model for a population divided into two subpopulations, immature and mature, and we apply this analysis to a model for platelet production. The dynamics of mature individuals is described by the following nonlinear differential equation with two delays: x (t) = −γx(t) + g(x(t − τ 1)) − g(x(t − τ 1 − τ 2))e −γτ 2. The method of D-decomposition is used to compute the stability regions for a given equilibrium. The centre manifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Holomorphic functions of the form (2) are known as quasipolynomials. For a quasipolynomial under the form (2), one usually defines its degree D as D = N + N j=0 d j , where, for j ∈ {1, . .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Holomorphic functions of the form (2) are known as quasipolynomials. For a quasipolynomial under the form (2), one usually defines its degree D as D = N + N j=0 d j , where, for j ∈ {1, . .…”
Section: Introductionmentioning
confidence: 99%
“…The relations between the notions of roots of maximal multiplicity and dominance have been explored in some recent works, such as [3,5,20,21], in which it is shown that, for some particular classes of quasipolynomials, a root with maximal multiplicity is dominant. More precisely, we say that a quasipolynomial verifies the multiplicity-induced-dominancy (MID) property if it possesses a (strictly) dominant root of maximal multiplicity, and the previous references prove the MID property for some quasipolynomials of the form (2) with N = 1, corresponding thus to delay-differential equations of the form (1) with a single delay. To the best of the authors' knowledge, extensions of the MID property to the case of multiple delays have not yet been considered in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this present work, we focus on cyclic erythropoiesis and design a model to explain this rarely observed disorder. To that purpose, we take advantage of relevant erythropoiesis mice, dogs and rabbit models (Bélair et al, 1995;Mahaffy et al, 1998;Fuertinger et al, 2013) and mathematical analysis specific to DDEs (Beretta and Kuang, 2002;Adimy et al, 2005;Crauste, 2010;Boullu et al, 2019a) Changes on parameter values accounting for the cyclic erythropoiesis have been well described: among these changes, one can note an increase of the hematopoietic stem cells apoptosis rate (Mackey, 1997) (mice and dogs) or a death rate amplification of mature red blood cells in the case of induced auto immune hemolytic anemia (Mackey, 1979) (rabbits). However, erythrocyte periodic oscillations specific to humans have been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%